Power Flow Analysis with Unified Power Flow Controller - Pandita, Adit (My University, 2013)
Flexible Alternating Current Transmission Systems (FACTS) have been proposed as an effective solution for controlling power flow and regulating bus voltage in electrical power systems. The use of FACTS is also intended to increase transfer capability, reduce losses, and improved stability. Unified Power Flow Controller (UPFC) is the most promising and effective FACTS system for power flow control. Various steady state models of UPFC that are suitable for incorporation in power flow programs are analyzed. The Comprehensive NR model of the UPFC is realized in MATLAB program. The power flow solution is based on Newton-Raphson method. The effectiveness of UPFC is studied on 5-Bus Test system. The UPFC is operated to control voltage magnitude and the line flow. The effect of UPFC placement has been studied. The effect of initial voltage of converter, the effect of converter reactance has been studied on power flow convergence.
Keywords: Power System; Newton-Raphson; UPFC; Steady State Model